2011
DOI: 10.1098/rsif.2011.0567
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of talin-1 to glioma cell–matrix tensional homeostasis

Abstract: The ability of cells to adapt their mechanical properties to those of the surrounding microenvironment (tensional homeostasis) has been implicated in the progression of a variety of solid tumours, including the brain tumour glioblastoma multiforme (GBM). GBM tumour cells are highly sensitive to extracellular matrix (ECM) stiffness and overexpress a variety of focal adhesion proteins, such as talin. While talin has been shown to play critical early roles in integrin-based force-sensing in non-tumour cells, it r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 45 publications
0
35
0
Order By: Relevance
“…CLU is a secreted molecular chaperone protein implicated in cancer [15,17,31,42,54,55] that we previously detected in the CSF proteome of DIPG patients [43]. TLN1 is a cytoskeletal protein that controls integrin activation to facilitate cell migration by promoting cell motility and adhesion in glioma [7,40,41,46,56]. Currently, therapeutic agents targeting integrins such as Cilengitide are under investigation as a treatment for adult high-grade astrocytoma (GBM).…”
Section: Discussionmentioning
confidence: 99%
“…CLU is a secreted molecular chaperone protein implicated in cancer [15,17,31,42,54,55] that we previously detected in the CSF proteome of DIPG patients [43]. TLN1 is a cytoskeletal protein that controls integrin activation to facilitate cell migration by promoting cell motility and adhesion in glioma [7,40,41,46,56]. Currently, therapeutic agents targeting integrins such as Cilengitide are under investigation as a treatment for adult high-grade astrocytoma (GBM).…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found that this mechanosensitivity was dependent on non-muscle myosin II-mediated cellular contractility, such that inhibition of contractility using the small-molecule drug blebbistatin rescued invasion on soft substrates. In follow-up studies, we have explored the role of the focal adhesion proteins α-actinin [107] and talin [108] in transducing mechanical cues, as well as the central role of the Rho GTPase RhoA in mediating the resulting contractility-dependent cellular phenotype [109]. As a potential caveat, a recent study suggested that changing the stiffness of the PAA substrate is potentially communicated to cells through alterations in the anchoring density of the tethered ECM protein [110].…”
Section: Engineering Strategies To Model the Gbm Microenvironmentmentioning
confidence: 99%
“…The resulting structures lead to alterations of the cell morphology and the generation of traction force necessary to move the cell body. Recent reports indicate that focal adhesion protein expression, like talin and alpha-actinin, is related to the invasiveness of glioma cells (111).…”
Section: Actin Rearrangement Adhesion Complexes and Cellular Protrumentioning
confidence: 99%